Mergers and Bank Performance: Evidence from The Indian Public Sector ‎Banks - Goswami, Manash Pratim; Mahapatra , Prof. Santosh Kumar (International Journal of Accounting and Economics Studies, 2025)
The existing literature on bank mergers reveals mixed and inconclusive evidence on merger ‎outcomes, particularly in developing economies. This study examines the impact of the 2020 ‎merger of Indian Public Sector Banks (PSBs), which remained largely underexplored. The ‎study employs a quantitative design with causal-comparative elements, utilising eight years (2016–2024). It applies the "Profit = Spread – Burden" framework to explore the drivers ‎of bank profitability after the mergers. CAMEL-based key performance ratios are also analysed using paired and independent-samples t-tests, and a difference-in-differences regression is employed to isolate merger effects. Findings indicate improved profitability primarily due to ‎increased spreads, alongside gains in capital adequacy and asset quality. Employee productivity rose without significant downsizing, though rising intermediation costs highlight operational challenges. A significant decline in the cost of funds (CF) highlights stronger bargaining power ‎and an improved ability of merged banks to mobilise funds at lower costs. Compared to non-‎merged banks, merger benefits appear moderate, questioning guaranteed scale efficiencies. ‎Thus, with a multi-layered analytical approach, this study provides insights into merger ‎outcomes for policymakers in evaluating the effectiveness of mergers as a reform tool, ‎especially in the Indian banking context.
Keywords: Bank Merger; Difference-in-Difference Regression; Financial Performance; India; Ratio ‎Analysis